Impact of miglustat on evolution of atypical presentation of late-infantile-onset Niemann–Pick disease type C with early cognitive impairment, behavioral dysfunction, epilepsy, ophthalmoplegia, and cerebellar involvement: a case report. (December 2016) - Cuisset, Jean-Marie; Sukno, S.; Trauffler, A.; Latour, P.; Dobbelaere, D.; Michaud, L.; Vallée, L.
Abstract Background Niemann–Pick disease type C is a rare inherited neurodegenerative disease involving impaired intracellular lipid trafficking and accumulation of glycolipids in various tissues, including the brain. Miglustat, a reversible inhibitor of glucosylceramide synthase, has been shown to be effective in the treatment of progressive neurological manifestations in pediatric and adult patients with Niemann–Pick disease type C, and has been used in that indication in Europe since 2010. Case presentation We describe the case of a 16-year-old white French boy with late-infantile-onset Niemann–Pick disease type C who had the unusual presentation of early-onset behavioral disturbance and learning difficulties (aged 5) alongside epileptic seizures. Over time he developed characteristic, progressive vertical ophthalmoplegia, ataxic gait, and cerebellar syndrome; at age 10 he was diagnosed as having Niemann–Pick disease type C based on filipin staining and genetic analysis (heterozygous I1061T/R934XNPC1 mutations). He was commenced on miglustat therapy aged 11 and over the course of approximately 3 years he showed a global improvement as well as improved cognitive and ambulatory function. During this period he remained seizure free on antiepileptic therapy, using valproate and lamotrigine. Conclusions Miglustat improved the neurological status of our patient, including seizure control. Based on our findings in this patient and previous published data, we discuss the importance of effective seizure control in neurological improvement in Niemann–Pick disease type C, and the relevance of cerebellar involvement as a possible link between these clinical phenomena. Thus the therapeutic efficacy of miglustat could be hypothesized as a substrate reduction effect on Purkinje cells.